2016
DOI: 10.1016/j.foodchem.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and bioactive compounds of garlic (Allium sativum L.) as affected by pre- and post-harvest conditions: A review

Abstract: Garlic (Allium sativum L.) is considered one of the twenty most important vegetables, with various uses throughout the world, either as raw vegetable for culinary purposes, as also an ingredient in traditional and modern medicine. Further, it has been also proposed as one of the richest sources of total phenolic compounds among the usually consumed vegetables, whereas highly ranked regarding its contribution of phenolic compounds in human diet. This review aims to examine all the aspects related with garlic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
278
2
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(295 citation statements)
references
References 62 publications
3
278
2
12
Order By: Relevance
“…The presence of orgasulfur compounds in other species motivated a wide cluster of studies mainly focused on health promoting effects [46,47,48,49]. These findings and the results presented in the present conference paper justify more pharmaceutical and nutraceutical researches as a new trend of investigation for M. alliacea.…”
Section: Discussionsupporting
confidence: 66%
“…The presence of orgasulfur compounds in other species motivated a wide cluster of studies mainly focused on health promoting effects [46,47,48,49]. These findings and the results presented in the present conference paper justify more pharmaceutical and nutraceutical researches as a new trend of investigation for M. alliacea.…”
Section: Discussionsupporting
confidence: 66%
“…Apart from the differences in antioxidant activity and TPC content between the various genotypes grown in different regions, significant variations were also observed between local cultivars (G1 and G2) and local landraces (G9-G11), which further supports the effect of genotype on these parameters apart from microclimate conditions and cultivations practices that usually differ between the various growing regions. Bhandari et al (2014) have also reported significant differences in chemical composition and antioxidant activity of garlic lines and cultivars, which could be attributed to adaptation mechanisms that may be developed throughout their cultivation history, as well as to artificial selection through vegetative propagation (Hirata et al, 2015) and preharvest factors (Beato et al, 2011;Martins et al, 2016). Furthermore, Khar, Banerjee, Jadhav, and Lawande (2011) who evaluated chemical composition of various Indian garlic ecotypes, reported significant variation between different genotypes, as well as significant bulb to bulb variation, especially in local landraces where breeding status and uniformity is generally low.…”
Section: Resultsmentioning
confidence: 99%
“…Although, the species originates from Central Asia, it is widely distributed and well adapted throughout the Mediterranean basin, while in Greece there are many regions where garlic is the main agricultural product and a part of popular culture throughout the centuries.So far, there is great interest in its therapeutic properties and health benefits and many reports confirm the beneficial effects of garlic and garlic related products, e.g. aged garlic extracts (AGE), garlic oils, essential oils and so forth against various diseases (Casella, Leonardi, Melai, Fratini, & Pistelli, 2013;El-Hamidi & El-Shami, 2015;Kopec, Piatkowska, Leszczynska, & Sikora, 2013;Kyung, 2012;Martins, Petropoulos, & Ferreira, 2016;Zeng et al, 2017). Moreover, considering the vegetative propagation of garlic, there is a great interest for local landraces and ecotypes regarding their bioactive compounds content and the importance of genetic material conservation (Baghalian, Naghavi, Ziai, & Badi, 2006;Baghalian, Ziai, Naghavi, & Naghdi Badi, 2005;Gonzalez, Soto, Sance, Camargo, & Galmarini, 2009;Kamenetsky et al, 2005).One of the major beneficial effects of garlic is related with antioxidant properties which have been tested in animal models and clinical studies with various forms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been proposed as one of the richest sources of total phenolic compounds, among the usually consumed vegetables, and has been highly ranked regarding its contribution of phenolic compounds to human diet. 1 Garlic is a particularly rich source of organosulfur compounds that are partly responsible for the beneficial effects of garlic on health and allicin is a reactive sulfur species (RSS). 2,3,4 Garlic essential oil which concentrates the bioactive components, presents also properties such as antibacterial, antifungal and antioxidant.…”
Section: Introductionmentioning
confidence: 99%